2017
DOI: 10.1097/md.0000000000007486
|View full text |Cite|
|
Sign up to set email alerts
|

Determining the relationship of kinesiophobia with respiratory functions and functional capacity in ankylosing spondylitis

Abstract: Ankylosing spondylitis (AS) is a common inflammatory rheumatic disease that affects the axial skeleton, causes inflammatory lower back pain, and structural and functional disorders, which affect quality of life negatively.The purpose of this study is to investigate the effects of kinesiophobia in AS on pulmonary function tests (PFTs) and functional performance.Thirty-one individuals with AS (n = 19 male, n = 12 female) who were suitable on the basis of the Modified New York (MNY) criteria were included in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 30 publications
(38 reference statements)
0
9
0
Order By: Relevance
“…9 In our study, differently from the studies by Er et al and Oskay et al, a significant correlation was found between kinesiophobia level and disease activity compared to the control group. 13,14 Although, when we categorized the patients into two groups according to the sacroiliitis grade and kinesiophobia level, there was no significant relationship between disease activity and higher scores. This could have been occurred due to the small sample size in the present study.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…9 In our study, differently from the studies by Er et al and Oskay et al, a significant correlation was found between kinesiophobia level and disease activity compared to the control group. 13,14 Although, when we categorized the patients into two groups according to the sacroiliitis grade and kinesiophobia level, there was no significant relationship between disease activity and higher scores. This could have been occurred due to the small sample size in the present study.…”
Section: Discussionmentioning
confidence: 89%
“…Oskay et al showed the impairment of the quality of life in the patients with ankylosing spondylitis due to the kinesiophobia. 13 In another study, no statistically significant relationship was reported between kinesiophobia scores and BASDAI (p>0.05), but there was a weak correlation with Bath Ankylosing Spondylitis Metrology Index (BASFI). 14 This study aims to determine kinesiophobia and its relationship with disease activity, quality of life, and pain scores in patients with AS.…”
Section: Ori̇ji̇nal Araştirma Original Researchmentioning
confidence: 92%
“…Er G. et al, investigated relation between kinesophobia and respiratory functions in AS (20-70 years). Their study did not find a significant relationship between TSK values and respirotary functions and endurance (21). Swinnen et al, reported that TSK-11 is a promising and valid tool to assess fearful beliefs in relation to activity limitations in axial spondyloarthropathy (22).…”
Section: Discussionmentioning
confidence: 93%
“…Individuals are not able to sustain the activities that they believe will increase their pain for a long time. Avoidance of long-duration movements leads to a reduction in motor activities due to physical (incapacity syndrome as a result of loss of mobility and muscle strength) and psychological (depression and loss of self-esteem) factors [12, 13]. Together with anatomical changes due to new bone formation, pain-related behavior represents an important aspect that should be taken into account in patients with axSpA starting physical therapy.…”
Section: Physiotherapy and Exercise In Axspamentioning
confidence: 99%